Készíts lapbookot! módszertani innováció a kreatív tanulásban - Illés Nóra (2020)
A lapbook is a book or an album created by the students themselves and related to a specific topic. But what is the secret of its growing popularity worldwide? In this publication, I am going to answer the most basic questions that arise with lapbooks. I am going to explain to which age group the making of lapbook is recommended. I am going to outline the areas of education where we can apply them. In addition, I am going to itemize, how to start applying lapbooks at primary and secondary school. Furthermore, I am going to share some technical ideas for making lapbooks without concealing its positive properties and risk factors. Last but not least, I am going to present a self-made lapbook.